2023
DOI: 10.1038/s41467-023-36767-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic band topology with non-trivial second Chern numbers

Abstract: Topological band theory establishes a standardized framework for classifying different types of topological matters. Recent investigations have shown that hyperbolic lattices in non-Euclidean space can also be characterized by hyperbolic Bloch theorem. This theory promotes the investigation of hyperbolic band topology, where hyperbolic topological band insulators protected by first Chern numbers have been proposed. Here, we report a new finding on the construction of hyperbolic topological band insulators with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…Recently, based on the similarity between circuit Laplacian and lattice Hamiltonian, simulating topological states with electric circuits has attracted lots of interest [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Compared with other classical platforms, circuit networks possess remarkable advantages of being versatile and reconfigurable.…”
Section: Based On the Above Results We Can Further Obtain Thatmentioning
confidence: 99%
“…Recently, based on the similarity between circuit Laplacian and lattice Hamiltonian, simulating topological states with electric circuits has attracted lots of interest [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Compared with other classical platforms, circuit networks possess remarkable advantages of being versatile and reconfigurable.…”
Section: Based On the Above Results We Can Further Obtain Thatmentioning
confidence: 99%
“…Hyperbolic lattices are an exotic class of lattices in non-Euclidean space with constant negative curvature, supporting tessellation of any regular p-site polygon with p > 2, which has been recently realized in circuit quantum electrodynamics and electric circuits [90][91][92][93][94]. In [67], it has been shown that HSTE can also emerge in hyperbolic Haldane models with sublattice-dependent gain and loss ±iγ.…”
Section: Hste In Hyperbolic Latticesmentioning
confidence: 99%
“…At present, the topological properties of topological insulators have been implemented in electrical circuit [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Topological circuits are primarily composed of inductor-capacitor(LC) networks and can be fabricated on printed circuit board (PCB), which offer the advantages of flexible design, inexpensive electronic components, and well-established technology, and are used to experimentally verify the existence of topological states.…”
Section: Introductionmentioning
confidence: 99%